Controlling Horizontal Dipole Orientation and Emission Spectrum of Ir Complexes by Chemical Design of Ancillary Ligands for Efficient Deep‐Blue Organic Light‐Emitting Diodes. Issue 21 (10th April 2019) - Shin, Hyun; Ha, Yeon Hee; Kim, Hyun‐Gu; Kim, Ran; Kwon, Soon‐Ki; Kim, Yun‐Hi; Kim, Jang‐Joo
Abstract: Deep‐blue emitting Iridium (Ir) complexes with horizontally oriented emitting dipoles are newly designed and synthesized through engineering of the ancillary ligand, where 2′, 6′‐difluoro‐4‐(trimethylsilyl)‐2, 3′‐bipyridine (dfpysipy) is used as the main ligand. Introduction of a trimethylsilyl group at the pyridine and a nitrogen at the difluoropyrido group increases the bandgap of the emitter, resulting in deep‐blue emission. Addition of a methyl group (mpic) to a picolinate (pic) ancillary ligand or replacement of an acetate structure of pic with a perfluoromethyl‐triazole structure (fptz) increases the horizontal component of the emitting dipoles in sequence of mpic (86%) > fptz (77%) > pic (74%). The organic light‐emitting diode (OLED) using the Ir complex with the mpic ancillary ligand shows the highest external quantum efficiency (31.9%) among the reported blue OLEDs with a y ‐coordinate value lower than 0.2 in the 1931 Commission Internationale de L'Eclairage (CIE) chromaticity diagram. Abstract : A deep‐blue iridium (Ir) complex with CIE coordinate y < 0.2 and horizontal emitting dipole ratio of 86% is developed by the chemical design of ancillary ligands. The phosphorescent organic light‐emitting diode (phOLED) using the Ir complex shows an external quantum efficiency of 31.9% with CIE y < 0.2, which is the highest value ever achieved in deep‐blue phOLEDs.